(untitled) (Bioresearch Communications, 2021)
Background: Every day more than 220 women around the world die from severe bleeding after childbirth. Globally post-partum hemorrhage is the number one direct cause of maternal mortality. Most postpartum hemorrhages are caused by uterine atony and occur in the immediate postpartum period. Most of these tragic deaths can be prevented by active management of third stage of labour. Active management of the third stage of labor should be practiced routinely to decrease the risk of postpartum hemorrhage. Oxytocin is used for enhancing uterine contraction after delivery. But oxytocin has some limitations like shorter half- life, less contraction time and more side effects, whereas carbetocin has prolonged duration of action which ensures more contraction time and less adverse effects. This study was done to see the efficacy and safety of carbetocin over oxytocin for prevention of PPH after vaginal delivery. Methodology: A randomized controlled clinical trial was conducted in the Department of Obstetrics and Gynecology, Shaheed Suhrawardy Medical College and Hospital, Dhaka, Bangladesh over a period of 9 months from January 2015 to September 2015. Ninety four patients undergoing vaginal delivery at term were randomized into two groups receiving either 10IU oxytocin or 100 μg carbetocin. Outcome measures such as primary PPH, massive blood loss, need for additional uterotonic drug, additional blood transfusion as well as adverse effects were documented. Results: In this study, massive blood loss did not occur none of patients in carbetocin group. But massive blood loss occured 6.4% women of oxytocin group. Further fundal massage , immediate blood transfusion and additional uterotonics didn’t need any patient in carbetocin group. In oxytocin group, fundal massage required in 8.5% of women, blood transfusion needed in 10.6% patients and additional uterotonics needed in 10.6% women. Average amount of blood loss was 88 ml less in carbetocin group and adverse effects of drugs were almost similar in both group. Primary PPH developed in oxytocin group 8.5% but none of patients had developed PPH in carbetocin group. Conclusion: Carbetocin is an effective new drug than oxytocin for prevention of postpartum hemorrhage in vaginal delivery. Bioresearch Commu. 7(1): 927-931, 2021 (January)